Turkey on the Way of Universal Health Coverage through the Health Transformation Program (2003-13) - Bump, Jesse (World Bank Group, Washington, DC, 2014)
Beginning in 2003, Turkey initiated a series of reforms under the Health Transformation Program (HTP) that over the past decade have led to the achievement of universal health coverage (UHC). The progress of Turkey s health system has few if any parallels in scope and speed. Before the reforms, Turkey s aggregate health indicators lagged behind those of OECD member states and other middle-income countries. The health financing system was fragmented, with four separate insurance schemes and a Green Card program for the poor, each with distinct benefits packages and access rules. Both the Ministry of Labor and Social Security and Ministry of Health (MoH) were providers and financiers of the health system, and four different ministries were directly involved in public health care delivery. Turkey s reform efforts have impacted virtually all aspects of the country s health system and have resulted in the rapid expansion of the proportion of the population covered and of the services to which they are entitled. At the same time, financial protection has improved. For example, (i) insurance coverage increased from 64 to 98 percent between 2002 and 2012; (ii) the share of pregnant women having four antenatal care visits increased from 54 to 82 percent between 2003 and 2010; and (iii) citizen satisfaction with health services increased from 39.5 to 75.9 percent between 2003 and 2011. Despite dramatic improvements there is still space for Turkey to continue to improve its citizens health outcomes, and challenges lie ahead for improving services beyond primary care. The main criticism to reform has so far come from health sector workers; the future sustainability of reform will rely not only on continued fiscal support to the health sector but also the maintenence of service provider satisfaction.